(untitled) (Povijesni prilozi (Historical Contributions), 2019)
The paper presents a chronological overview of portraits of Empress Maria Theresia in museum collections of north-western Croatia – Zagreb, Varaždin and Trakošćan. The early portraits of Maria Th eresia as the heiress to the throne are smaller in size, portraying her as the Austrian archduchess, while portraits after her ascension to the throne are mostly large, stressing the offi cial use they were intended for. They range in quality from those painted by well-known Viennese court artists up to representations by highly or less skilled anonymous artists. Martin van Meytens the Younger stands out as the most prominent portraitist of the Empress; together with his workshop he provided the whole Austrian Empire with numerous portraits of Maria Theresia and her husband. Most of her portraits painted between 1741 and 1760, held in museum collections in north-western Croatia, are attributed to Meytens and / or his workshop. Portraits of Empress Maria Theresia in museum collections of north-western Croatia present the monarch in different stages of her life – as a young archduchess and heiress to the throne, a mighty ruler and mother, and fi nally a grieving widow. They remain a constant reminder of the greatness she had achieved as the only female monarch of the vast multinational Habsburg Empire.